Negative electrode slurry mixing method
By stepping the flow rate of deionized water in the negative electrode slurry combination process of lithium-ion batteries, the problems of large fineness and fast settlement caused by large-particle graphite are solved, and the production of high-quality slurry and battery performance are improved.
Patent Information
- Application Number
- CN202411897948.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the production of lithium-ion batteries, a fixed flow rate setting value is used in the negative electrode slurry combination process. When the particle size of the graphite incoming material is too large, the slurry fineness and fast settlement, which affects the coating stability and the electrode stripping test results.
The flow rate of deionized water is adjusted step by step in the twin-screw extruder, first increasing and then decreasing, forming wetted powder and kneaded powder, increasing the solid content of the side feeding, and optimizing the slurry particle size and fineness.
It has achieved the production of high-quality slurries with small fineness, small particle size and small settlement, improved coating stability and electrode stripping strength, and improved equipment capabilities and battery performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery manufacturing, and in particular to a negative electrode slurry mixing method. Background Art
[0002] In the process of preparing lithium batteries, the dispersion and uniformity of the granular active materials in the positive and negative electrode slurries directly affect the movement of lithium ions between the two poles of the battery. Therefore, the mixing and dispersion of the slurries of various electrode materials is very important in the production of lithium-ion batteries. The quality of the slurry dispersion directly affects the quality of subsequent lithium-ion battery production and the performance of its products. Therefore, in the process of preparing electrode sheets, the mixing and dispersion quality of lithium-ion battery slurries must be controlled to improve the uniformity and dispersion stability of battery slurries.
[0003] At present, lithium-ion battery manufacturers mainly use the twin-screw extruder continuous pulping method. The twin-screw extruder continuous pulping divides the traditional batch pulping into several small parts, disperses them continuously, and then summarizes them into a whole batch. It is significantly superior to the traditional process in pulping efficiency and pulping uniformity.
[0004] At present, the deionized water for the negative electrode slurry is added at each water inlet of the twin-screw extruder, and a process with a fixed flow rate setting value is adopted. The slurry produced by this process has good consistency, stable viscosity and solid content, and good production continuity. However, when the slurry process with a fixed setting value is adopted, when the particle size of the incoming graphite material is too large, when the side feed setting value is increased to a certain value, the starting current of the main screw increases significantly, the screw is stuck, and the machine cannot be started for production, which is likely to cause damage to the equipment; and the prepared slurry has a large fineness and fast sedimentation, which is easy to cause frequent scraping during subsequent coating, increased feeding pressure, poor coating stability, and abnormal electrode peeling test after coating, which urgently needs to be improved. Summary of the invention
[0005] Based on this, in view of the current negative electrode slurry mixing process, deionized water adopts a fixed flow rate setting value in the side feeding and main screw input. When the particle size of the incoming graphite is relatively large, the prepared slurry has a large fineness and settles quickly, which can easily lead to frequent scraping in subsequent coating, increased feeding pressure, poor coating stability, and abnormal electrode sheet peeling test after coating. The present invention provides a negative electrode slurry mixing method.
[0006] To achieve the above object, the present invention adopts the following technical solutions: The present invention first provides a negative electrode slurry mixing method, which comprises the following steps: S1. The powder material is added to the feed port of the twin-screw extruder for dry mixing, and the dry mixed powder is conveyed to the twin-screw extruder for pre-kneading; S2. Add deionized water for wetting and control the flow gradient of deionized water to decrease to form a wet powder; S3. Add deionized water for kneading and control the flow rate of deionized water to increase and then decrease to form a kneaded powder; S4. SBR and deionized water were added to obtain a semi-finished slurry from the discharge port of the twin-screw extruder; S5. The semi-finished slurry is passed into a homogenizer for dispersion; S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing to obtain negative electrode slurry.
[0007] As a further improvement of the above scheme of the present invention, in step S2, the flow rate of the deionized water is controlled to increase from an initial flow rate to a second gradient flow rate, and then decrease to a third gradient flow rate. The initial flow rate is 270-282 kg / h, the second gradient flow rate is 304-346 kg / h, and the third gradient flow rate is 222-255 kg / h.
[0008] As a further improvement of the above scheme of the present invention, in step S3, the flow rate of the deionized water is controlled to increase from an initial flow rate to a second gradient flow rate, and then decrease to a third gradient flow rate. The initial flow rate is 195-246 kg / h, the second gradient flow rate is 201-252 kg / h, and the third gradient flow rate is 180-196 kg / h.
[0009] As a further improvement of the above scheme of the present invention, in step S4, the side feeding port three is located at the eighth barrel section of the twin-screw extruder, the solid content of the semi-finished slurry is 52%-56%, the viscosity is 2000-5000mPa·s, and the fineness is less than 35μm.
[0010] As a further improvement of the above solution of the present invention, in step S1, the powder material includes graphite, a conductive agent and a binder.
[0011] As a further improvement of the above solution of the present invention, the particle size D90 of the graphite is 28-30 μm, and Dmax is 54-60 μm.
[0012] As a further improvement of the above solution of the present invention, in step S1, the flow rate of the graphite is 675±3.375 kg / h, the flow rate of the conductive agent is 3.5±0.017 kg / h, and the flow rate of the binder is 8.4±0.042 kg / h.
[0013] As a further improvement of the above solution of the present invention, in step S4, the flow rate of the SBR is 26.3±0.132 kg / h.
[0014] As a further improvement of the above scheme of the present invention, the speed of the twin-screw extruder is 600±10 rpm; the speed of the homogenizer is 4500±50 rpm; the orbital speed of the dispersion kettle is 25±2 rpm, the rotation speed is 1200±20 rpm, the vacuum degree is ≤-0.090 Mpa, and the dispersion time is 2-3h.
[0015] As a further improvement of the above solution of the present invention, in steps S1-S5, the temperature of the slurry is controlled at 20-50°C.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention aims at large-particle graphite. By step-adjusting the flow rate of deionized water, the solid content of the side feed is gradually increased, the grinding effect is enhanced, the slurry particle size, fineness, sedimentation and other properties are optimized, the coating stability and the electrode peeling strength are improved, and the equipment capacity is further improved without changing the original structure and rated power of the slurry mixer, so as to produce high-quality slurry with small fineness, small particle size and small sedimentation. DETAILED DESCRIPTION
[0017] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0019] Example 1 This embodiment provides a negative electrode slurry mixing method, comprising the following steps: S1. Add graphite, conductive agent SP and binder CMC to the feed port of a twin-screw extruder for dry mixing, with the flow rate of graphite being 675kg / h, the flow rate of conductive agent being 3.5kg / h, and the flow rate of binder being 8.4kg / h; convey the dry-mixed powder to the twin-screw extruder for pre-kneading and dispersion. The speed of the twin-screw extruder is 6000rpm, and the slurry temperature is controlled at 40°C.
[0020] S2. Add deionized water from the water inlet of the second barrel of the twin-screw extruder to wet the powder, and control the initial flow rate of deionized water to 282 kg / h, the second gradient flow rate to 346 kg / h, the third gradient flow rate to 255 kg / h, and the interval between two adjacent gradients to be 3 min.
[0021] S3. Deionized water was added from the water inlet of the seventh barrel of the twin-screw extruder for kneading and dispersion to form a kneaded powder. The initial flow rate of deionized water was controlled to be 195 kg / h, the second gradient flow rate was 221 kg / h, the third gradient flow rate was 180 kg / h, and the interval time between two adjacent gradients was 3 min.
[0022] S4. Add SBR and deionized water from the eighth barrel of the twin-screw extruder, control the flow rate of SBR to 26.3 kg / h, the flow rate of deionized water to 84 kg / h, discharge the material from the discharge port of the twin-screw extruder, and obtain a semi-finished slurry. The semi-finished slurry has a solid content of 58%, a viscosity of 3241 mPa·s, and a fineness of 25 μm.
[0023] S5. The semi-finished slurry is passed into a homogenizer with a rotation speed of 4500 rpm for dispersion, wherein the slurry temperature is controlled at 40°C.
[0024] S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing. The orbital speed of the dispersion kettle is 25 rpm, the rotation speed is 1200 rpm, the vacuum degree is ≤-0.090 Mpa, the dispersion time is 3 hours, and the slurry temperature is controlled at 40°C.
[0025] Example 2 This embodiment provides a negative electrode slurry mixing method, comprising the following steps: S1. Add graphite, conductive agent SP and binder CMC to the feed port of a twin-screw extruder for dry mixing, with the flow rate of graphite being 675kg / h, the flow rate of conductive agent being 3.5kg / h, and the flow rate of binder being 8.4kg / h; convey the dry-mixed powder to the twin-screw extruder for pre-kneading and dispersion. The speed of the twin-screw extruder is 6000rpm, and the slurry temperature is controlled at 40°C.
[0026] S2. Add deionized water from the water inlet of the second barrel of the twin-screw extruder to wet the powder, and control the initial flow rate of deionized water to 270 kg / h, the second gradient flow rate to 320 kg / h, the third gradient flow rate to 252 kg / h, and the interval between two adjacent gradients to be 3 min.
[0027] S3. Deionized water was added from the water inlet of the seventh barrel of the twin-screw extruder for kneading and dispersion to form a kneaded powder. The initial flow rate of deionized water was controlled to be 246 kg / h, the second gradient flow rate was 201 kg / h, the third gradient flow rate was 190 kg / h, and the interval time between two adjacent gradients was 3 min.
[0028] S4. Add SBR and deionized water from the eighth barrel of the twin-screw extruder, control the flow rate of SBR to 26.3 kg / h, the flow rate of deionized water to 84 kg / h, discharge the material from the discharge port of the twin-screw extruder, and obtain a semi-finished slurry. The semi-finished slurry has a solid content of 58%, a viscosity of 2980 mPa·s, and a fineness of 20 μm.
[0029] S5. The semi-finished slurry is passed into a homogenizer with a rotation speed of 4500 rpm for dispersion, wherein the slurry temperature is controlled at 40°C.
[0030] S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing. The orbital speed of the dispersion kettle is 25 rpm, the rotation speed is 1200 rpm, the vacuum degree is ≤-0.090 Mpa, the dispersion time is 3 hours, and the slurry temperature is controlled at 40°C.
[0031] Example 3 This embodiment provides a negative electrode slurry mixing method, comprising the following steps: S1. Add graphite, conductive agent SP and binder CMC to the feed port of a twin-screw extruder for dry mixing, with the flow rate of graphite being 675kg / h, the flow rate of conductive agent being 3.5kg / h, and the flow rate of binder being 8.4kg / h; convey the dry-mixed powder to the twin-screw extruder for pre-kneading and dispersion. The speed of the twin-screw extruder is 6000rpm, and the slurry temperature is controlled at 40°C.
[0032] S2. Add deionized water from the water inlet of the second barrel of the twin-screw extruder to wet the powder, and control the initial flow rate of deionized water to 276 kg / h, the second gradient flow rate to 304 kg / h, the third gradient flow rate to 222 kg / h, and the interval between two adjacent gradients to be 3 min.
[0033] S3. Deionized water was added from the water inlet of the seventh barrel of the twin-screw extruder for kneading and dispersion to form a kneaded powder. The initial flow rate of deionized water was controlled to be 230 kg / h, the second gradient flow rate was 252 kg / h, the third gradient flow rate was 196 kg / h, and the interval time between two adjacent gradients was 3 min.
[0034] S4. Add SBR and deionized water from the eighth barrel of the twin-screw extruder, control the flow rate of SBR to 26.3 kg / h, the flow rate of deionized water to 84 kg / h, discharge the material from the discharge port of the twin-screw extruder, and obtain a semi-finished slurry. The semi-finished slurry has a solid content of 58%, a viscosity of 3012 mPa·s, and a fineness of 22 μm.
[0035] S5. The semi-finished slurry is passed into a homogenizer with a rotation speed of 4500 rpm for dispersion, wherein the slurry temperature is controlled at 40°C.
[0036] S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing. The orbital speed of the dispersion kettle is 25 rpm, the rotation speed is 1200 rpm, the vacuum degree is ≤-0.090 Mpa, the dispersion time is 3 hours, and the slurry temperature is controlled at 40°C.
[0037] Comparative Example 1 This comparative example provides a negative electrode slurry preparation method, comprising the following steps: S1. Add graphite, conductive agent SP and binder CMC to the feed port of a twin-screw extruder for dry mixing, with the flow rate of graphite being 652kg / h, the flow rate of conductive agent being 3.38kg / h, and the flow rate of binder being 8.1kg / h; convey the dry-mixed powder to the twin-screw extruder for pre-kneading and dispersion. The speed of the twin-screw extruder is 6000rpm, and the slurry temperature is controlled at 40°C.
[0038] S2. Add deionized water from the water inlet of the second barrel of the twin-screw extruder to wet the powder and form a wet powder. The flow rate of deionized water is controlled to be 342 g / h.
[0039] S3. Deionized water was added from the water inlet of the seventh barrel of the twin-screw extruder for kneading and dispersion to form a kneaded powder, and the flow rate of deionized water was controlled to be 175 g / h.
[0040] S4. Add SBR and deionized water from the eighth barrel of the twin-screw extruder, control the flow rate of SBR to 25.3 kg / h, the flow rate of deionized water to 84 kg / h, discharge the material from the discharge port of the twin-screw extruder to obtain a semi-finished slurry. The semi-finished slurry has a solid content of 56%, a viscosity of 3400 mPa·s, and a fineness of 36 μm.
[0041] S5. The semi-finished slurry is passed into a homogenizer with a rotation speed of 4500 rpm for dispersion, wherein the slurry temperature is controlled at 40°C.
[0042] S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing. The orbital speed of the dispersion kettle is 25 rpm, the rotation speed is 1200 rpm, the vacuum degree is ≤-0.090 Mpa, the dispersion time is 3 hours, and the slurry temperature is controlled at 40°C.
[0043] Comparative Example 2 This comparative example provides a negative electrode slurry preparation method, comprising the following steps: S1. Add graphite, conductive agent SP and binder CMC to the feed port of a twin-screw extruder for dry mixing, with the flow rate of graphite being 652kg / h, the flow rate of conductive agent being 3.38kg / h, and the flow rate of binder being 8.1kg / h; convey the dry-mixed powder to the twin-screw extruder for pre-kneading and dispersion. The speed of the twin-screw extruder is 6000rpm, and the slurry temperature is controlled at 40°C.
[0044] S2. Deionized water was added from the water inlet of the second barrel of the twin-screw extruder to wet the powder, and the flow rate of the deionized water was controlled to be 327 kg / h.
[0045] S3. Deionized water was added from the water inlet of the seventh barrel of the twin-screw extruder for kneading and dispersion to form a kneaded powder, and the flow rate of deionized water was controlled to be 191 kg / h.
[0046] S4. Add SBR and deionized water from the eighth barrel of the twin-screw extruder, control the flow rate of SBR to 25.3 kg / h, the flow rate of deionized water to 84 kg / h, discharge the material from the discharge port of the twin-screw extruder, and obtain a semi-finished slurry. The semi-finished slurry has a solid content of 56%, a viscosity of 3568 mPa·s, and a fineness of 32 μm.
[0047] S5. The semi-finished slurry is passed into a homogenizer with a rotation speed of 4500 rpm for dispersion, wherein the slurry temperature is controlled at 40°C.
[0048] S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing. The orbital speed of the dispersion kettle is 25 rpm, the rotation speed is 1200 rpm, the vacuum degree is ≤-0.090 Mpa, the dispersion time is 3 hours, and the slurry temperature is controlled at 40°C.
[0049] Comparative Example 3 This comparative example provides a negative electrode slurry preparation method, comprising the following steps: S1. Add graphite, conductive agent SP and binder CMC to the feed port of a twin-screw extruder for dry mixing, with the flow rate of graphite being 652kg / h, the flow rate of conductive agent being 3.38kg / h, and the flow rate of binder being 8.1kg / h; convey the dry-mixed powder to the twin-screw extruder for pre-kneading and dispersion. The speed of the twin-screw extruder is 6000rpm, and the slurry temperature is controlled at 40°C.
[0050] S2. Deionized water was added from the water inlet of the second barrel of the twin-screw extruder to wet the powder, and the flow rate of the deionized water was controlled to be 312 kg / h.
[0051] S3. Deionized water was added from the water inlet of the seventh barrel of the twin-screw extruder for kneading and dispersion to form a kneaded powder, and the flow rate of deionized water was controlled to 206 kg / h.
[0052] S4. Add SBR and deionized water from the eighth barrel of the twin-screw extruder, control the flow rate of SBR to 25.3 kg / h, the flow rate of deionized water to 84 kg / h, discharge the material from the discharge port of the twin-screw extruder, and obtain a semi-finished slurry. The semi-finished slurry has a solid content of 56%, a viscosity of 4200 mPa·s, and a fineness of 31 μm.
[0053] S5. The semi-finished slurry is passed into a homogenizer with a rotation speed of 4500 rpm for dispersion, wherein the slurry temperature is controlled at 40°C.
[0054] S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing. The orbital speed of the dispersion kettle is 25 rpm, the rotation speed is 1200 rpm, the vacuum degree is ≤-0.090 Mpa, the dispersion time is 3 hours, and the slurry temperature is controlled at 40°C.
[0055] Test Case The negative electrode slurry prepared in the above Examples 1-3 and Comparative Examples 1-3 is coated on copper foil to prepare a negative electrode sheet; the positive electrode is lithium iron phosphate, and the ingredient ratio (weight ratio) of the positive electrode slurry is LFP:SP:GOs (solid content):PVDF =96.8:0.7:0.5:2.0, which is mixed and coated on aluminum foil; the electrolyte uses LiPF6 electrolyte (main components: EC, PC, EMC, DMC, LiPF6, LiPSI, VC, MMDS, FB), the diaphragm is PP+coated diaphragm, assembled into batteries and the battery performance is tested, the battery capacity test method is: the battery is transferred to the capacity division area through the elevator and the conveyor line, the capacity division cabinet is equipped with a stacker to automatically put the pallet carrying the battery on the cabinet, and the capacity division temperature is (24±3)℃; the capacity division is carried out according to the production line capacity division process, 10,000 batteries per batch, and the standard deviation of the battery capacity of each batch is calculated. The negative electrode slurry coating results and battery consistency test results are shown in Table 1.
[0056] Table 1
[0057] It can be seen from the results in Table 1 that after the solid content is increased according to the gradient, the viscosity of the slurry is reduced, the solid content is increased, and the fineness is reduced. In the process of coating the trolley, the pressure of the feeding pump is reduced from the original 240-280KPa to 230-240KPa, and the fineness of the slurry is reduced from the original 30-36 microns to 20-25 microns. The coating effect is improved from the original scraping frequency (5-6 times / batch) to the current (0-1 time / batch). At the same time, the capacity consistency of the battery cell is also improved, and the capacity standard deviation is reduced from the original 0.90Ah to 0.48Ah. The negative electrode slurry mixing method of the present invention improves the utilization level of the battery cell.
[0058] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A negative electrode slurry preparation method, characterized in that: It includes the following steps: S1. The powder material is added to the feed port of the twin-screw extruder for dry mixing, and the dry mixed powder is conveyed to the twin-screw extruder for pre-kneading; S2. Add deionized water for wetting and control the flow rate of deionized water to increase and then decrease to form a wet powder; S3. Add deionized water for kneading and control the flow rate of deionized water to increase and then decrease to form a kneaded powder; S4. SBR and deionized water were added to obtain a semi-finished slurry from the discharge port of the twin-screw extruder; S5. The semi-finished slurry is passed into a homogenizer for dispersion; S6. The slurry dispersed by the homogenizer is pumped into a dispersion kettle for dispersion and degassing to obtain negative electrode slurry.
2. The negative electrode slurry mixing method according to claim 1, characterized in that: In step S2, the flow rate of the deionized water is controlled to increase from an initial flow rate to a second gradient flow rate, and then decrease to a third gradient flow rate. The initial flow rate is 270-282 kg / h, the second gradient flow rate is 304-346 kg / h, and the third gradient flow rate is 222-255 kg / h.
3. The negative electrode slurry mixing method according to claim 1, characterized in that: In step S3, the flow rate of the deionized water is controlled to increase from an initial flow rate to a second gradient flow rate, and then decrease to a third gradient flow rate. The initial flow rate is 195-246 kg / h, the second gradient flow rate is 201-252 kg / h, and the third gradient flow rate is 180-196 kg / h.
4. The negative electrode slurry mixing method according to claim 1, characterized in that: In step S4, the semi-finished product slurry has a solid content of 52%-56%, a viscosity of 2000-5000 mPa·s, and a fineness of less than 35 μm.
5. The negative electrode slurry mixing method according to claim 1, characterized in that: In step S1, the powder material includes graphite, a conductive agent and a binder.
6. The negative electrode slurry mixing method according to claim 5, characterized in that: The graphite has a particle size D90 of 28-30 μm and a Dmax of 54-60 μm.
7. The negative electrode slurry mixing method according to claim 5, characterized in that: In step S1, the flow rate of the graphite is 675±3.375 kg / h, the flow rate of the conductive agent is 3.5±0.017 kg / h, and the flow rate of the binder is 8.4±0.042 kg / h.
8. The negative electrode slurry mixing method according to claim 1, characterized in that: In step S4, the flow rate of the SBR is 26.3±0.132 kg / h.
9. The negative electrode slurry mixing method according to claim 1, characterized in that: The speed of the twin-screw extruder is 600±10 rpm; the speed of the homogenizer is 4500±50 rpm; the speed of the dispersion kettle is 25±2rpm for revolution and 1200±20 rpm for rotation, the vacuum degree is ≤-0.090 Mpa, and the dispersion time is 2-3h.
10. The negative electrode slurry mixing method according to claim 1, characterized in that: In steps S1-S5, the temperature of the slurry is controlled at 20-50°C.
Citation Information
Patent Citations
Lithium ion battery negative electrode paste preparation process
CN108807997A
Lithium battery negative electrode slurry dry preparation method
CN112397676A
Aqueous homogenate process of lithium ion battery positive electrode system, slurry and lithium battery
CN115722093A
Sodium-ion battery negative electrode slurry and preparation method thereof
CN116014126A
Homogenizing process of negative electrode slurry
CN117358078A
Cited By
Battery slurry mixing method, battery slurry and negative plate
CN122068020A